Carbon nanofiber heating film with nano tenon-and-mortise structure and preparation method of carbon nanofiber heating film

Through the preparation method of the carbon nanofiber heating film of nano-monomer and tenon structure, the problems of uneven dispersion and high interfacial thermal resistance in the polymer matrix are solved, and the thermal and electrical conductivity and the stability of mechanical properties are significantly improved.

CN120273108AActive Publication Date: 2025-07-08DONGHUA UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510629868.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-16
Publication Date
2025-07-08
Estimated Expiration
2045-05-16

AI Technical Summary

Technical Problem

In practical applications, carbon nanofiber films have problems such as high interface thermal resistance, difficulty in uniform dispersion of fibers in polymer matrix, structural heterogeneity leads to performance differences and insufficient shear strength, which affects their thermal conductivity, electrical conductivity and mechanical properties.

Method used

The preparation method of nano-monomer and tenon structure carbon nanofiber heating film is adopted, and a new strategy of free surface electrospinning and in-situ carbonization growth is formed to form a carbon nanotube synapse embedded in the adjacent fiber surface, combining non-precious metal transition metal-based nitrogen/oxygen co-doped carbon nanotubes with the carbon nanofiber membrane to form a three-dimensional heat transfer network.

Benefits of technology

The thermal conductivity of carbon nanofiber membranes is significantly improved (the thermal conductivity in thickness is increased by 80%-200%), electrical conductivity (resistivity is reduced by 1-2 orders of magnitude) and mechanical properties (resistivity is improved by improving anti-bending stability), achieving more uniform thermal conductivity and higher current carrying capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120273108A_ABST
    Figure CN120273108A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nanometer materials and heat management, in particular to a preparation method of a carbon nanofiber heating film with a nanometer mortise and tenon joint structure, a two-stage mortise and tenon joint structure is formed through metal catalysis in-situ growth of carbon nanotubes, and a three-dimensional interpenetrating network between fibers is achieved. The method specifically comprises the following steps: preparing a polymer precursor fiber membrane containing transition metal salt by adopting a free surface electrostatic spinning technology, performing pre-oxidation, and performing melamine-assisted high-temperature carbonization to catalyze and grow a pod-shaped carbon nano tube branch on the surface of a carbon nano fiber to form a mortise and tenon type mechanical interlocking and chemical bonding synergistic interface. According to the structure, the contact area between fibers is increased, the heat conductivity coefficient in the thickness direction and the transverse conductivity are improved, and meanwhile, the mechanical strength is high. No insulating adhesive is introduced, the process is compatible with an existing production line, and the method can be widely applied to the fields of high-power electronic heat dissipation, flexible device heat management and energy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials and thermal management, and particularly to a nano mortise and tenon structure carbon nanofiber heating film and a preparation method thereof. Background Art

[0002] Carbon nanofibers have extremely high thermal conductivity along the axial direction. For example, the axial thermal conductivity of pitch-based carbon fibers can exceed 1000 W / m·K, approaching the level of single-crystal graphite. Its dense structure and low defect characteristics (such as the ordered arrangement of multi-layer graphite sheets) effectively reduce phonon scattering and improve the heat transfer efficiency. In terms of electrical conductivity, the resistivity of carbon nanofibers can be as low as 0.1–0.37 Ω·cm, and the conductivity is as high as 200 S / m, which benefits from its highly graphitized carbon skeleton and three-dimensional conductive network structure. By doping materials such as graphene or carbon nanotubes, its conductivity can be further enhanced. For example, a shielding efficiency of up to 84.5 dB can be achieved in electromagnetic shielding materials. Its high specific surface area and close contact between fibers also reduce the interfacial resistance, making it suitable for flexible electronic devices and lithium-ion battery electrodes.

[0003] However, the films made of carbon nanofibers face the following bottlenecks in practical applications: First, the electrical and thermal conductivity of carbon nanofibers show significant directionality. In macroscopic materials, carbon nanofibers only rely on van der Waals force contact between fibers, resulting in high interfacial thermal resistance. The thermal conductivity along the fiber axis can reach more than 1000 W / m·K, but the thermal conductivity in the perpendicular direction is only 8–15 W / m·K. Similarly, its electrical conductivity is prone to high interfacial resistance in the contact area between fibers, and the transverse conductivity is less than 1% of the axial direction.

[0004] Moreover, the high aspect ratio and surface energy of carbon nanofibers make them prone to winding and agglomeration, and it is difficult to disperse uniformly in the polymer matrix, resulting in limited thermal / electrical conductivity of the composite material. For example, after adding 3% carbon nanofibers to epoxy resin, the thermal conductivity of the composite material is increased from 0.2 W / m·K to 0.6 W / m·K, which is still far lower than the theoretical value of single carbon nanofibers.

[0005] At the same time, the diameter, arrangement density and defects of carbon nanofibers will directly affect the uniformity of electrical and thermal conductivity. The carbon nanofiber film faces the problem of performance differences caused by structural heterogeneity. For example, the disordered fiber network may form local electrical / thermal conductivity bottlenecks, reducing the overall efficiency. Finally, there is a lack of physical interlocking between the layers of traditional carbon nanofiber films, and the shear strength is less than 30 MPa, which is prone to slip under dynamic loads, affecting long-term reliability. Summary of the Invention

[0006] Aiming at the deficiencies of the prior art, the present invention provides a nano mortise and tenon structure carbon nanofiber heating film and a preparation method thereof, which solve the problems of high interfacial thermal resistance of carbon nanofiber films and the difficulty of uniformly dispersing carbon nanofibers in the polymer matrix.

[0007] To achieve the above objectives, the present invention is realized through the following technical solutions: A preparation method of a nano mortise and tenon structure carbon nanofiber heating film, comprising the following steps: S1. Preparation of the precursor solution First, dissolve polyacrylonitrile and cellulose acetate in a DMF solvent, then add metal acetylacetonate, stir at a temperature of 60 °C to promote the dissociation of polymer chains, form a homogeneous solution, stir until the metal ions are uniformly dispersed in the polymer network, and measure the solution viscosity through a rotational rheometer, controlling it at about 3000 mPa·s to ensure the stability of the jet during spinning.

[0008] S2. Free surface electrospinning Adopt a porous stepped spinneret, use the liquid surface tension to form multiple jets. The spinneret is made of stainless steel. The non-woven fabric collector uses a high-speed rotating drum with a linear velocity of 10 m / s to randomly stack the fibers, forming a three-dimensional fluffy structure, which is beneficial to the gas diffusion during subsequent carbonization. The electrospinning voltage is 85 - 90 kv. The ultra-high electric field stretches and refines the solution jet, reducing the diameter from the millimeter level to the nanometer level. The distance between the spinneret and the collector is 20 - 30 cm to ensure sufficient stretching of the jet and solvent evaporation. The flow rate of 60 mL / h matches the electric field strength. Too high a flow rate will form droplets, and too low a flow rate will result in a decrease in productivity.

[0009] S3. Pre-oxidation treatment Introduce an air atmosphere into the pre-oxidation furnace to perform pre-oxidation treatment on the fiber membrane. The heating rate is 1 - 3 °C / min, and the final temperature is 250 - 300 °C. In a high-temperature environment, the cyano group of polyacrylonitrile undergoes a cyclization reaction to form a ladder structure, improving the thermal stability. The acetyl group in cellulose acetate undergoes thermal decomposition to generate CO2 and H2O, and at the same time, micropores are formed on the fiber surface. At the same time, some metals (such as Fe) are oxidized to Fe2O3, providing a precursor for the subsequent carbonization to generate Fe3C.

[0010] S4. In-situ growth carbonization The pre-oxidized fiber membrane and melamine are placed in an inert atmosphere for carbonization. The carbonization temperature is 700-900℃, the heating rate is 5-10℃ / min, and the constant temperature time is 1-3 hours. The carbon nanotube branches are grown in situ by catalysis. Melamine decomposes into gases such as NH3, HCN and C2N2 above 600℃, providing nitrogen and carbon sources. NH3 reacts with the carbon skeleton to form active sites such as pyridine nitrogen (N-6) and pyrrole nitrogen (N-5), which improves the ORR / OER catalytic activity. HCN cracks to provide carbon atoms, and metal particles catalyze their growth into CNTs along a specific crystal direction. During the heating stage, fiber oxidation can be avoided under the protection of N2. At the same time, the flow rate of N2 is controlled in the range of 200-500sccm to ensure the stability of the reduction environment of the metal particles. Melamine begins to decompose at 300-500℃ and releases gas. At 700°C, Fe2O3 is reduced to Fe by carbon, and part of Fe reacts with C to form Fe3C. The Fe / Fe3C interface serves as a catalyst for CNT growth. At 800°C, CNTs begin to grow, and Fe particles are wrapped by graphite layers to prevent oxidation and deactivation. Carbon atoms adsorb, diffuse, and precipitate on the metal surface to form CNTs. At the same time, the gas produced by the decomposition of cellulose acetate forms pores inside the fiber, with a pore size distribution of 10-100 nm, increasing the exposure of active sites and forming a pod structure.

[0011] The present invention provides a nano-mortise and tenon structure carbon nanofiber heating film and a preparation method thereof. It has the following beneficial effects: The present invention embeds carbon nanotube synapses into the surface of adjacent fibers in a mortise and tenon manner, increasing the contact area by 5-10 times; the synapse length and density are optimized synergistically, and the interface contact resistance is reduced to 0.05-0.1Ω·cm by four-probe method testing. 2 .

[0012] The present invention adopts a new strategy of free-surface electrospinning combined with in-situ carbonization growth to prepare on a large scale independent bifunctional catalysts (MNO-CNT-CNFFs) composed of non-noble transition metal-based nitrogen / oxygen co-doped carbon nanotubes (CNTs) and carbon nanofiber membranes.

[0013] In the present invention, Fe nanoparticles are wrapped in graphite layers at a carbonization temperature of 800° C., and CNTs grown in situ form a "peapod-like" structure, thereby increasing active site exposure and specific surface area. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a SEM electron microscope image of the carbon nanofiber heating film prepared in the present invention, wherein a is a schematic diagram of carbon nanotube synapses embedded in the surface of adjacent fibers in the form of mortise and tenon, and b is an enlarged schematic diagram of a single fiber. DETAILED DESCRIPTION

[0015] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention. Embodiment

[0016] The embodiment of the present invention provides a preparation method of an iron-based nano mortise and tenon structure carbon nanofiber heating film, including the following steps: S1. Preparation of precursor solution Dissolve 6 g of polyacrylonitrile and 6 g of cellulose acetate in 100 mL of DMF solvent, and stir at 60 °C for 4 hours until completely dissolved. Add 5 g of iron acetylacetonate and continue to stir for 12 hours to form a homogeneous spinning solution.

[0017] S2. Free surface electrospinning Adopt a stepped spinneret, apply a high voltage of 85 - 90 kV, the flow rate of the spinning solution is 60 mL / h, and the distance between the spinneret and the grounded non-woven fabric collector is 25 cm. Continuously electrospin for 60 minutes to obtain an Fe-enriched nanofiber membrane with a size of 180 cm × 80 cm.

[0018] S3. Stabilization treatment Place the Fe-enriched nanofiber membrane in an air oven, heat it to 280 °C at a rate of 1 °C / min, and keep it at a constant temperature for 2 hours to obtain a pre-oxidized fiber membrane.

[0019] S4. In-situ carbonization and CNT growth Place the pre-oxidized membrane in a porcelain boat, lay 1 g of melamine at the bottom, and the mass ratio of the pre-oxidized membrane to melamine is 1:5. Heat it to 800 °C at a rate of 5 °C / min under N2 protection and keep it at a constant temperature for 2 hours. Cool to room temperature to obtain FeNO-CNT-CNFF-800, on the surface of which "pod-shaped" carbon nanotubes with a diameter of 10 - 30 nm grow uniformly (Fe nanoparticles are coated inside 4 - 6 layers of graphite shells).

[0020] Measured data: Thermal conductivity: The thermal conductivity in the thickness direction is 25 W / m·K, which is 80% higher than that of the traditional membrane, indicating that the three-dimensional heat transfer network is more uniform.

[0021] Electrical conductivity: The resistivity measured by the four-probe method is 5.2×10 -3 Ω·cm, which is about one order of magnitude lower than that of the unmodified membrane (1×10 -2 Ω·cm); at a current density of 10 A / cm², the temperature rise is less than 5 °C, which is more stable and has a stronger current-carrying capacity than the traditional membrane.

[0022] Mechanical properties: The resistance change rate is less than 2% after 2000 bending cycles under the condition of a curvature radius of 0.5 mm. Example

[0023] The embodiment of the present invention provides a preparation method of a cobalt-based carbon nanofiber heating film with a nano mortise and tenon structure, including the following steps: S1. Preparation of precursor solution Referring to Example 1, the difference is that 5 g of cobalt acetylacetonate is added and stirring is continued for 12 hours to form a homogeneous spinning solution.

[0024] S2. Electrospinning and stabilization Referring to Example 1, the difference is that a Co-enriched nanofiber membrane is prepared and pre-oxidized.

[0025] S3. Optimization of carbonization process The pre-oxidized membrane is placed in a porcelain boat, and 1 g of melamine is laid at the bottom. The mass ratio of the pre-oxidized membrane to melamine is 1:5. In an N2 atmosphere, it is heated to 700 °C at a rate of 5 °C / min and kept at a constant temperature for 2 hours. CoNO-CNT-CNFF-700 is obtained, in which the CNTs grow shorter (length < 100 nm), but the surface is enriched with Co-N x Active sites (the N content detected by XPS is 4.8 at.%).

[0026] Measured data: Thermal conductivity: The thermal conductivity in the thickness direction is 20 W / m·K, which is 50%-70% higher than that of the traditional heating film, indicating that the Co-based material optimizes the interfacial heat transfer path through pyridine nitrogen doping.

[0027] Conductivity: The transverse conductivity measured by the four-probe method is 1.5×10³ S / m, which is one order of magnitude higher than that of the unmodified film; at a current density of 5 A / cm², the temperature rise is 8-10 °C, and the stability is better than that of the traditional heating film. Example

[0028] The embodiment of the present invention provides a preparation method of a nickel-based carbon nanofiber heating film with a nano mortise and tenon structure, including the following steps: S1. Precursor solution and spinning Referring to Example 1, the difference is that 5 g of nickel acetylacetonate is added and stirring is continued for 12 hours to form a homogeneous spinning solution.

[0029] S2. Electrospinning and stabilization Referring to Example 1, the difference is that a Ni-enriched nanofiber membrane is prepared and pre-oxidized.

[0030] S3. High-temperature carbonization regulation Place the pre-oxidized film in a porcelain boat, lay 2 g of melamine at the bottom, with the mass ratio of the pre-oxidized film to melamine being 1:10. Heat it to 900 °C at a rate of 5 °C / min under N2 protection and keep it at a constant temperature for 2 hours.

[0031] In the obtained NiNO-CNT-CNFF-900, the length of CNTs increased significantly by 500 nm, and the degree of graphitization increased (Raman ID / IG = 1.139). The surface Ni-N x accounts for 9.0% (XPS analysis).

[0032] Measured data: Thermal conductivity: The thermal conductivity in the thickness direction is 32 W / m·K.

[0033] Electrical conductivity: The transverse electrical conductivity measured by the four-probe method reaches 1×10 4 S / m, which is two orders of magnitude higher than that of the unmodified film.

[0034] Although the embodiments of the present invention have been shown and described, those of ordinary skill in the art can understand that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention. The scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. The carbon nanofiber heating film with a nano mortise and tenon structure is characterized in that: Comprising: A carbon nanofiber matrix formed by blending and carbonizing polyacrylonitrile and cellulose acetate, with a fiber diameter of 100 - 500 nm; Carbon nanotube branched structure, the carbon nanotube branched structure grows in-situ on the surface of carbon nanofibers to form a mortise and tenon interlocking network, the length of the carbon nanotube branches is 50 - 200 nm, and the density is 10 5 -10 7 / cm 2 ; Metal nanoparticles selected from at least one of Fe, Co, and Ni, with a particle size of 10 - 50 nm, and the metal nanoparticles are embedded at the ends of carbon nanotubes or on the surface of carbon nanofibers; A nitrogen and oxygen co-doped carbon skeleton with a nitrogen content of 4.8 - 9.0 at.% and an oxygen content of 2.5 - 5.3 at.%, forming a three-dimensional conductive / heat-conductive network.

2. The carbon nanofiber heating film with a nano mortise and tenon structure according to claim 1, wherein: The contact interface between the carbon nanotube branches and the adjacent carbon nanofibers includes the synergistic effect of chemical bonding and mechanical interlocking, and the interfacial contact resistance is 0.05 - 0.1 Ω·cm 2 , and the thermal conductivity in the thickness direction is 20 - 30 W / m·K.

3. The preparation method of the nano mortise and tenon structure carbon nanofiber heating film according to claim 1, characterized in that: Including the following steps: S1. Dissolve polyacrylonitrile, cellulose acetate, and metal acetylacetonate in a DMF solvent to prepare a spinning precursor solution; S2. Prepare a nanofiber membrane by free surface electrospinning technology, with an electrospinning voltage of 85 - 90 kV and a distance between the spinneret and the collector of 20 - 30 cm; S3. Conduct pre-oxidation treatment on the fiber membrane in a pre-oxidation furnace under an air atmosphere, with a heating rate of 1 - 3 °C / min and a final temperature of 250 - 300 °C; S4. Co-carbidize the pre-oxidized fiber membrane and melamine in an inert atmosphere, with a carbonization temperature of 700 - 900 °C, a heating rate of 5 - 10 °C / min, and an isothermal time of 1 - 3 hours, for in-situ catalytic growth of carbon nanotube branches.

4. The preparation method of the nano mortise and tenon structure carbon nanofiber heating film according to claim 3, characterized in that: In the step S1, the metal acetylacetonate is at least one of Fe(Acac)3, Co(Acac)2, and Ni(Acac)2, and its addition amount is 10 - 30% of the total mass of the polymer.

5. The preparation method of the nano-mortise-and-tenon structure carbon nanofiber heating film according to claim 3, wherein: In the step S4, the mass ratio of melamine to the pre-oxidized fiber membrane is 1:(5 - 10), and the NH3 and HCN gases generated by the decomposition of melamine during the carbonization process serve as nitrogen and carbon sources.

6. The preparation method of the nano mortise and tenon structure carbon nanofiber heating film according to claim 3, characterized in that: In the step S2, the electrospinning uses a stepped porous spinneret with a pore diameter of 0.5 - 1.0 mm, a spinning solution flow rate of 50 - 80 mL / h, and a collector linear velocity ≥ 10 m / s.

7. The preparation method of the nano mortise and tenon structure carbon nanofiber heating film according to claim 3, characterized in that: In the step S4, the metal nanoparticles formed after carbonization are wrapped by 4 - 6 layers of graphite shells, and the ID / IG value of the graphitization degree of the carbon nanotube branches is 1.0 - 1.

2.

8. The application of the nano-mortise and tenon structure carbon nanofiber heating membrane according to any one of claims 1 - 2 in a heating sheet, a flexible circuit board, or a lithium-ion battery electrode, wherein the resistance change rate of the carbon nanofiber heating membrane after 2000 bending cycles is ≤ 2%.

Citation Information

Cited By

  • Waste fiber-based three-dimensional flexible functional carbon felt and preparation method thereof

    CN120591961A